Screamboat [videorecording (DVD)] - Garcia-Dunn, Matthew; LaMort, Steven; Schumacher, Amy; Thornton, David Howard, 1979-; Pittel, Allison; Posey, Jesse (Deskpop Entertainment, 2025)
Be our guest on a New York City ferry ride that turns into a hilarious nightmare when a mischievous mouse named Steamboat Willie becomes a monstrous reality. As passengers set sail, their trip turns deadly when the tiny terror unleashes murder & mayhem. Packed with big kills, big laughs, and a miniature menace, Screamboat is a cinematic thrill ride - reimagining Steamboat Willie like never before!